Global Governance in the Twenty-first Century
XI, 295 p.
Keywords: The key challenges of globalization are diffuse and outside the control of any one state. In its most ambitious and forward looking form, global governance seeks to create an international social fabric, albeit imperfect, which cumulatively, amounts to more than the sum of its parts. Global Governance in the Twenty-first-century aims to open a number of new areas for further analysis, and in particular, to begin a process of cross-fertilization between different disciplines examining issues related to global governance.